Nomina Bahasa Mooi: Mooi Language Noun - Mariati S., Sitti (Balai Bahasa Provinsi Papua, 2024)
This research aims to describe nouns in Mooi language. The research apply qualitative using descriptive method with three strategic stages, which are data collection, data analysis, and presentation of the results of data analysis. To collect the data, the whole conversation method and note-taking techniques were used. To analyze the data, the Agih Method was used with the direct element Agih technique. Based on the results of the analysis, the nouns of the Mooi language in terms of form consist of nouns which are basic word and nouns which are derivative word. The morphological processes that produce derivative nouns in Mooi are repetition and compounding. Nouns in terms of syntax behavior are determined based on their position or usage at the level of phrases and sentences. In nominal phrases, nouns have a function as the core or axis of the phrase. In sentences, nouns in terms of syntactic behavior can replace the functions of subject (S), object (O), and complement (Pel). In terms of semantics, the main meaning components of nouns in the Mooi language are divided into eight types, specifically people, animals, plants, fruits, tools, food, geography, and raw materials.